ANALISIS BEBERAPA UNSUR KIMIA KOMPOS Azolla mycrophylla - Sri Utami Lestari; muryanto muryanto (Universitas Lancang Kuning, 2018)
The most consumed part of the plants is the leaf part so that the fertilizer provided should contain high nitrogen (N). The nature of the N fertilizer is volatile and when the rainy season there can be washing. When plants deficienci nutrients shows symtoms of yellowing leaves so that the application of N fertilizer to the plant must remain unfulfilled. Azolla is a usable alternative. Azolla has a high N nutrient content because it is symbiotic with anabaena in binding to free nitrogen in the air. The purpose of this study was to determine the chemical composition (pH,N,P,K) Azolla mycrophylla. The experiment was conducted experimentally with the first stage of composting azolla after it was done chemical analysis in the laboratory. The result of this research can be concluded that chemical analysis of Azolla mycrophylla cpmpost is as follows :pH 7,17, N 2,57%, P 0,34%, K 0,03%.